Comparison of shear bond strength of different types of intracanal posts in restoring extensively damaged primary anterior teeth - Shabnam Asghari Mollabashi; Shima Nourmohamadi; Afrooz Nakhostin (Tabriz University of Medical Sciences, 2024)
Background. Severe caries in early childhood is a concern for both children receiving dental treatment and their parents. This dental disease progresses rapidly and quickly damages the coronal part of the tooth. When there is insufficient coronal structure to support a coronal restoration, using intracanal components following root canal treatment increases tooth resistance and helps provide retention for the coronal restoration. This study compared the shear bond strength of three types of intracanal posts (composite resin post, reverse metal post, and fiber post) in severely damaged primary anterior teeth. Methods. This in vitro study was conducted on 30 extracted anterior primary teeth with at least two-thirds of healthy roots and no prior pulp treatment. The teeth were randomly divided into three groups of 10: group 1: composite resin post with 8th generation universal bonding, group 2: reverse metal post with GC restorative glass cement, and group 3: fiber post with GC restorative glass cement. After placing the post, the samples were restored with a height of 3 mm from cementoenamel junction (CEJ) using an Anterior GC Gradia Packable composite resin. All the samples underwent 500 cycles of thermocycling in a hot water bath at 55±2 °C and a cold water bath at 5±2 °C. The shear strength of the samples was then evaluated using an electromechanical universal testing machine at a rate of 1 mm/min and at a location 2 mm coronal to the CEJ in terms of megapascals. Results. The average shear bond strength of composite resin posts with 8th generation bonding application was 8.02220 MPa, reverse metal posts with glass ionomer application was 13.8600 MPa, and fiber posts with glass ionomer application was 9.7400 MPa. Conclusion. Based on these findings, it can be concluded that the highest shear bond strength in this study was related to the reverse metal post, and the lowest shear bond strength was related to the composite resin post. According to the results, reverse metal posts demonstrated better shear bond strength than composite resin posts and fiber posts (P<0.05).